Cenários de gestão de escolas municipais no Brasil: questionário contextual da prova Brasil - Martins, Angela Maria; Sousa, Sandra Zákia; Machado, Cristiane; Real, Giselle Cristina Martins; Bravo, Maria Helena Aguiar (Fundação Carlos Chagas, 2018)
ABSTRACT This article discusses the results of a study that characterized management settings in municipal schools in Brazil, based on principals’ responses to the contextual questionnaire of Prova Brasil 2015. The purpose of this study was to analyze the potential of the practices reported in the instrument to contribute to the democratization of education. After the identification of limits in the constructs of the items, this instrument brought information on: profile data, education and professional trajectories; participation of families and other community members in the management of schools; initiatives that affect the access and permanence of students in school with guaranteed learning. We used the IBM SPSS Statistics-20 software, a program designed to perform statistical analysis.

RESUMEN Este artículo discute resultados de un estudio que caracterizó escenarios de gestión vigentes en escuelas municipales en Brasil, en base a respuestas de los directores al cuestionario contextual de la Prova Brasil de 2015. Tuvo el propósito de analizar la potencialidad de prácticas declaradas en el instrumento para contribuir con la democratización de la educación. Luego de identificar límites en los constructos de los ítems, el referido instrumento aportó subsidios para el examen de datos de perfil, trayectorias de formación y profesional; participación de familias y demás miembros de la comunidad en la gestión de las escuelas; iniciativas que inciden en el acceso y permanencia de los alumnos en la escuela con garantía del aprendizaje. Se utilizó el software IBM SPSS Statistics-20, programa desarrollado para realizar análisis estadísticos.

RÉSUMÉ Cet article présente les résultats d’une étude sur les scénarios de gestion en place dans des écoles communales au Brésil caracterisées a partir des réponses fournies par les directeurs au questionnaire contextuel de l´examen Prova Brasil de 2015. Son but était d’analyser la potentialité d es pratiques déclarées dans cet instrument afin de contribuer à la démocratisation de l’éducation. Cet instrument a permis non seulement d’identifier les limites présentes dans l’élaboration de ses items, mais aussi de procurer des informations pour examiner: les données sur le profil, les trajectoires de formation et professionnelles; la participation des familles et d’autres membres de la communauté dans la gestion des écoles; les initiatives jouant un rôle dans l’accès et le maintien des élèves à l’école tout en assurant l’apprentissage. Le logiciel IBM SPSS Statistics-20, a été utilisé pour l´analyse statistique.

RESUMO Este artigo discute resultados de estudo que caracterizou cenários de gestão vigentes em escolas municipais no Brasil, com base em respostas dos diretores ao questionário contextual da Prova Brasil de 2015. Teve como propósito analisar a potencialidade de práticas declaradas no instrumento para contribuir com a democratização da educação. Identificados limites nos constructos dos itens, o referido instrumento trouxe subsídios para exame de: dados de perfil, trajetórias de formação e profissional; participação de famílias e demais membros da comunidade na gestão das escolas; iniciativas que incidem no acesso e permanência dos alunos na escola com garantia da aprendizagem. Utilizou-se o software IBM SPSS Statistics-20, programa desenvolvido para realizar análises estatísticas.
Settings of management of municipal schools in Brazil: the contextual questionnaire of prova Brazil.
Escenarios de gestión de escuelas municipales en Brasil: cuestionario contextual de la prova Brasil
Keywords: Management; Municipal Schools; Prova Brasil; Gestão; Escolas Municipais; Prova Brasil